The effects of human height and mass on the calculated induced electric fields at 50 Hz for comparison with the EMF Directive 2013/35/EU. (24th January 2017) - Findlay, R P
Abstract: A worker's height and mass can significantly affect the way in which incident low frequency electric and magnetic fields are absorbed in the body. To investigate this, several anatomically realistic human models were produced for heights between 1.56 and 1.96 m and masses between 33 and 113 kg. The human models were derived from the MAXWEL surface-based phantom, the model previously used in the EMF Directive 2013/35/EU Practical Guide to demonstrate how induced electric fields in the body are calculated. Computer simulations were carried out to calculate the low frequency EMF directive exposure limit value (ELV) quantities, i.e. the induced electric fields, in these human model variations from exposure to external 50 Hz magnetic and electric fields. The computational work showed that simple relationships relating the human model's height/weight with the induced electric fields in tissue types such as bone, fat, muscle, brain, spinal cord and retina could be developed. Calculations of parameters that affected absorption and fields required to produce the EMF Directive ELVs were carried out and compared with the action levels (ALs). It was found that the ALs generally provided a conservative estimate of the ELVs for the various human models and exposure situations studied.